Novel delivery systems for phages and lysins in the topical management of wound infections: a narrative review - Yang, Pan; Li, Jing; Ma, Xiumei; Hu, Nan; Song, Zhangyong; Chen, Bin; Li, Shizhu (Frontiers in Microbiology, 2025)
Currently, multidrug-resistant (MDR) bacterial wound infections (WIs) are an extremely challenging clinical problem for physicians. Recently, compared to traditional single liquid delivery drugs, the study of five novel drug delivery systems (i.e., hydrogel, liposomes, electrospun fibers, nanoparticles and nanoemulsion) for phages and their encoded lysins in WI management has become a hot topic. To assess the current landscape of these emerging technologies, we conducted a comprehensive literature search across PubMed, Scopus and Web of Science up to July 2024, using terms such as “phage,” “lysin,” “wound,” “hydrogel,” “liposomes,” “fibers,” “nanoparticles,” and “nanoemulsion.” The criteria included original studies of five novel delivery systems for phages and lysins in WI management. The findings highlighted the positive effects of the five novel delivery systems for phages and lysins in WI management, significantly reducing wound bacterial populations, and accelerating healing at the injury site. However, the available literature on novel delivery systems for phages and lysins remains limited, particularly for lysins. In conclusion, the application of novel drug delivery systems for phages and lysins showed great potential in combating MDR bacterial WIs.